Remote Instrument Control with CIMA Web Services and Web 2.0 Technology - du Boulay, Douglas John; Brockhauser, Sandor; Chee, Clinton; Chiu, Kenneth; Devadithya, Tharaka; Leow, Richard; McMullen, Donald Frederick; Quilici, Romain; Turner, Peter (International Journal of Online and Biomedical Engineering (iJOE), 2008)
The Common Instrument Middleware Architecture (CIMA) model for Web services based monitoring of remote scientific instruments is being extended and enhanced to provide a capability for remote instrument control. X-ray diffraction has been selected as an ideal domain for prototype development, with the goal being a comprehensive and feature rich portal system for access to remote instruments and their data. The system has two principle components, one of which serves the instrument and data, and the second serves the client user. Plugin modules are used to provide flexibility and re-use, and the notion of plugin control is being developed. The architecture supports remote access to multiple instruments from a single portal. The use of Web 2.0 Pushlet and AJAX technologies has been introduced for push based portlet refresh and updating. An X3D based 3D virtual representation of the instrument provides data collection simulation and (pseudo) real time instrument representation.